GAMBARAN DAN TINGKAT KEPARAHAN CEDERA JARINGAN LUNAK PADA PASIEN DENGAN TRAUMA MAKSILOFASIAL YANG DIRAWAT DI BANGSAL BEDAH RSUD ARIFIN ACHMAD PEKANBARU PERIODE 2010-2013 - ", Susilawati; Pamungkas, Kuswan Ambar; Burhanuddin, Laode (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Maxillofacial trauma not only caused physical impact but also psychological impact. Velocity and accuracy in handling facial soft tissue trauma will very influential to the aesthetics and facial function. This study aimed at knowing the representation and severity degree of soft tissue injury in patients with maxillofacial trauma hospitalized in surgical ward RSUD Arifin Achmad since 2010-2013. This study was a descriptive retrospective study. This study used 413 medical records of maxillofacial trauma patients. Result from this study, samples in this study was 328 cases (79,23%) males, and 86 cases females (20,77%). The most common age was 11-20 years old (38,41%) whereas the most common etiology of maxillofacial trauma was traffic accidents (81,40%). Most of the patients’ occupation weren’t written in the medical records (48,55%), followed by students as many as 79 cases (19,08%). The most affected hard tissue was multiple fractures as many as (32,37%), whereas medium category of soft tissue injury was the most affected (55,31%) and the most often location was multiple as many as (37,68%). Key words : maxillofacial trauma, soft tissue injury, multiple fracture